A CONVERSATION WITH MARSHALL GOLDSMITH ABOUT LIVING AN EARNED LIFE. Issue 107 (7th December 2022) - Goldsmith, Marshall; McArthur, Sarah
Abstract: This article is a conversation with Marshall Goldsmith, one of the world's leading executive educators, coaches, and authors; and Leader to Leader co‐editor‐in‐chief Sarah McArthur, Goldsmith's former managing editor. They discuss the principles behind Goldsmith's new, best‐selling book The Earned Life . "We are living an earned life, " according to Goldsmith, "when the choices, risks, and effort we make in each moment align with an overarching purpose in our lives, regardless of the eventual outcome." He continues: "Experience has taught me that there is at least one universal baseline motivation guaranteed to clarify our desire to live an earned life, and to make progress toward an overarching purpose and it is this: We want to live a life that will increase our fulfillment and minimize our regret." Goldsmith relates the background to one of his most significant initiatives: "A number of years ago I started the 100 Coaches pay‐it‐forward community. It didn't start as the 100 Coaches; it started as 15 Coaches. In fact, it didn't even start as 15 Coaches, it started as an idea, a desire to connect my daily activities to a greater purpose." He also points personal heroes: "Alan Mulally, Frances Hesselbein, Jim Yong Kim, Paul Hersey, Peter Drucker, and of course Buddha."